Age-Dependent Changes in the Histogram of Apparent Diffusion Coefficients Values in Magnetic Resonance Imaging - Klose, Uwe; Batra, Marion; Nägele, Thomas (Frontiers in Aging Neuroscience, 2013)
The aim of this study was to develop a fast method for estimating whether a brain volume loss is within the normal range for the respective age of the patient. A readout-segmented diffusion weighted EPI sequence was performed as part of the routine examination at a 3T scanner. Data without (B0-image) and with diffusion weighting (1000 s/mm2) from 492 patients were examined. 173 data sets had to be excluded due to brain lesions or to pathological enlarged CSF spaces. In the remaining 319 data sets, ADC values were calculated for all pixels exceeding a combined threshold in the diffusion weighted data and in the non-diffusion weighted data. The first part of the histogram represents pixels containing mostly brain tissue. The percentage of number of pixels in this part of the ADC histograms was evaluated for all patients and was correlated with the age of the patients. In all the areas examined, a monotone change of relative pixel numbers with the age of the patients was found. The reduction of the contribution of pixels containing mostly brain tissue accelerated with age and was found to be 0.18%/year in the age of 20, 0.34%/year in the age of 50, and 0.50%/year in the age of 80. The observed decrease of voxel from brain tissue with increasing age corresponds to previously published results based on more time-consuming 3-D measurements. The presented technique uses a conventional clinical sequence and might be helpful in deciding whether an observed brain volume loss in a patient is within the normal range for the age of the patient.